Assessing a norming intervention to promote acceptance of HIV testing and reduce stigma during household tuberculosis contact investigation: protocol for a cluster-randomised trial - Armstrong-Hough, Mari; Ggita, Joseph; Gupta, Amanda J.; Shelby, Tyler; Nangendo, Joanita; Okello Ayen, Daniel; Davis, J. L.; Katamba, Achilles (BMJ Open, 2022)
HIV status awareness is important for household contacts of patients with tuberculosis (TB). Home HIV testing during TB contact investigation increases HIV status awareness. Social interactions during home visits may influence perceived stigma and uptake of HIV testing. We designed an intervention to normalise and facilitate uptake of home HIV testing with five components: guided selection of first tester; prosocial invitation scripts; opt-out framing; optional sharing of decisions to test; and masking of decisions not to test. Methods and analysis We will evaluate the intervention effect in a household-randomised controlled trial. The primary aim is to assess whether contacts offered HIV testing using the norming strategy will accept HIV testing more often than those offered testing using standard strategies. Approximately 198 households will be enrolled through three public health facilities in Kampala, Uganda. Households will be randomised to receive the norming or standard strategy and visited by a community health worker (CHW) assigned to that strategy. Eligible contacts ≥15 years will be offered optional, free, home HIV testing. The primary outcome, proportion of contacts accepting HIV testing, will be assessed by CHWs and analysed using an intention-to- treat approach. Secondary outcomes will be changes in perceived HIV stigma, changes in perceived TB stigma, effects of perceived HIV stigma on HIV test uptake, effects of perceived TB stigma on HIV test uptake and proportions of first-invited contacts who accept HIV testing. Results will inform new, scalable strategies for delivering HIV testing. Ethics and dissemination This study was approved by the Yale Human Investigation Committee (2000024852), Makerere University School of Public Health Institutional Review Board (661) and Uganda National Council on Science and Technology (HS2567). All participants, including patients and their household contacts, will provide verbal informed consent. Results will be submitted to a peer-reviewed journal and disseminated to national stakeholders, including policy-makers and representatives of affected communities.
Keywords: Norming intervention; HIV testing; Stigma; Household tuberculosis contact; Cluster-randomised trial